2018
DOI: 10.1093/dnares/dsx056
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals infection strategy of an insect maculavirus

Abstract: Bombyx mori macula-like virus (BmMLV) is a positive, single-stranded insect RNA virus that is closely related to plant maculaviruses. BmMLV is currently characterized as an unclassified maculavirus. BmMLV accumulates at extremely high levels in cell lines derived from the silkworm, Bombyx mori, but it does not lead to lethality and establishes persistent infections. It is unknown how this insect maculavirus replicates and establishes persistent infections in insect cells. Here, we showed that BmMLV p15, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 43 publications
5
74
0
Order By: Relevance
“…On the other hand, studies in several mosquito species have provided redundant proofs that the piRNA pathway is a key mechanism in their antiviral strategy to survive otherwise lethal infections (Aguiar et al, ; Brackney et al, ; Dietrich, Jansen, et al, ; Dietrich, Shi, et al, ; Joosten et al, ; Leger et al, ; Miesen et al, ; Morazzani et al, ; Schnettler, Donald, et al, ; Schnettler, Ratinier, et al, ; Schnettler et al, ; Scott et al, ; Varjak, Maringer, et al, ; Vodovar et al, ; Y. Wang et al, ). Recently, data on the antiviral properties of piRNAs in the silkworm B. mori have also started to accumulate, showing the possibility that piRNAs could act as antivirals also in insect groups other than mosquitoes (Katsuma et al, ). However, examples of no involvement of piRNAs in the control of viral infections also accumulate, since observations in an infected C. sonorensis (midge) cell line showed that, even if PIWI components are expressed, the piRNA pathway is probably not active against the infecting viruses (Dietrich, Shi, et al, ; Schnettler, Ratinier, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, studies in several mosquito species have provided redundant proofs that the piRNA pathway is a key mechanism in their antiviral strategy to survive otherwise lethal infections (Aguiar et al, ; Brackney et al, ; Dietrich, Jansen, et al, ; Dietrich, Shi, et al, ; Joosten et al, ; Leger et al, ; Miesen et al, ; Morazzani et al, ; Schnettler, Donald, et al, ; Schnettler, Ratinier, et al, ; Schnettler et al, ; Scott et al, ; Varjak, Maringer, et al, ; Vodovar et al, ; Y. Wang et al, ). Recently, data on the antiviral properties of piRNAs in the silkworm B. mori have also started to accumulate, showing the possibility that piRNAs could act as antivirals also in insect groups other than mosquitoes (Katsuma et al, ). However, examples of no involvement of piRNAs in the control of viral infections also accumulate, since observations in an infected C. sonorensis (midge) cell line showed that, even if PIWI components are expressed, the piRNA pathway is probably not active against the infecting viruses (Dietrich, Shi, et al, ; Schnettler, Ratinier, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data could indicate that flavivirus infections are relatively refractory to piRNA pathway activation. Finally, although the number of vpiRNA‐related studies in the order of Lepidoptera is limited, it is apparent that BmN4 cells produce BmMLV‐specific vpiRNAs with a Ping‐Pong pattern where Siwi is mainly found to bind 1U‐sense and BmAgo3 to bind preferentially 10A‐antisense vpiRNAs (Katsuma et al, ). However, neither in Bm5 cells nor in B. mori larvae was any evidence for an active Ping‐Pong mechanism detected (L. Wang et al, ; Zografidis et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractionation replicates correlate very well (average Pearson correlation coe cient >0.97) ( Fig 3A) and cluster together in the rst two PCA dimensions ( Fig 3B). Within the gradient, fraction series [1][2][3], [4][5][6][7] and [8][9] are similar to each other, while fraction 10 is most different from all others. This is consistent with fraction 10 constituting an acetone precipitation of all proteins that were not separated in the previous fractionation steps.…”
Section: Subcellular Localization Of Proteins Determined By Lopit-dcmentioning
confidence: 92%